2020
DOI: 10.1016/j.cell.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Robust T Cell Immunity in Convalescent Individuals with Asymptomatic or Mild COVID-19

Abstract: SUMMARY SARS-CoV-2-specific memory T cells will likely prove critical for long-term immune protection against COVID-19. We here systematically mapped the functional and phenotypic landscape of SARS-CoV-2-specific T cell responses in unexposed individuals, exposed family members, and individuals with acute or convalescent COVID-19. Acute phase SARS-CoV-2-specific T cells displayed a highly activated cytotoxic phenotype that correlated with various clinical markers of disease severity, whereas convale… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

101
1,171
4
16

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,625 publications
(1,343 citation statements)
references
References 57 publications
(79 reference statements)
101
1,171
4
16
Order By: Relevance
“…Accumulating information on the antibody response against SARS-CoV-2 demonstrates that structural proteins such as the spike and nucleoprotein serve as potent antibody targets in a substantial fraction of COVID-19 patients [2][3][4][5][6] . However, much less is currently known regarding the SARS-CoV-2-speci c T cell response, in particular which parts of the virus are targeted by T cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating information on the antibody response against SARS-CoV-2 demonstrates that structural proteins such as the spike and nucleoprotein serve as potent antibody targets in a substantial fraction of COVID-19 patients [2][3][4][5][6] . However, much less is currently known regarding the SARS-CoV-2-speci c T cell response, in particular which parts of the virus are targeted by T cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, much less is currently known regarding the SARS-CoV-2-speci c T cell response, in particular which parts of the virus are targeted by T cells. Both CD4 and CD8 T cells can recognize SARS-CoV-2 derived antigens 4,[6][7][8][9][10][11][12][13] . Most studies have focused on limited parts of the viral proteome 6,8,12 , and in particular the spike protein 4,10,13 , which was found to be a very important antigen source for virus speci c T cell responses in SARS-CoV-1 14 and MERS 15 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, within-individual variation has been observed in immune responses to viral exposure, particularly in those with mild or asymptomatic disease. For example, a pilot study from the Karolinska Institute found the percentage of people mounting T cell responses after mild covid-19, asymptomatic disease, or exposure to infected family members, consistently exceeded the percentage mounting detectable IgG serological responses against the virus 3. Such discordant results could have major implications for epidemiological modelling of disease transmission and herd immunity.…”
mentioning
confidence: 99%